2013
DOI: 10.1186/1471-2296-14-81
|View full text |Cite
|
Sign up to set email alerts
|

General practitioner’s clinical practices, difficulties and educational needs to manage Alzheimer’s disease in France: analysis of national telephone-inquiry data

Abstract: BackgroundThe literature has emphasized the role of general practitioners (GPs) in caring for Alzheimer’s disease (AD) patients. Within the framework of the French national AD plan, an inquiry was undertaken to identify the clinical practices, difficulties and training needs of GPs managing this pathology.MethodsA random sample from a representative national listing of continental French GPs following ≥1 AD patients comprised the study population. Participants completed a standard questionnaire on their clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…However, we know that the diagnostic rates of dementia, although improving, are low . Furthermore, although the majority of people with dementia wish to know the diagnosis, GPs can be reluctant to fully disclose it . Secondly, GPs may be reluctant to initiate a conversation about BPSD unless they feel comfortable giving practical advice to family caregivers on managing BPSD, something many GPs struggle with .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we know that the diagnostic rates of dementia, although improving, are low . Furthermore, although the majority of people with dementia wish to know the diagnosis, GPs can be reluctant to fully disclose it . Secondly, GPs may be reluctant to initiate a conversation about BPSD unless they feel comfortable giving practical advice to family caregivers on managing BPSD, something many GPs struggle with .…”
Section: Discussionmentioning
confidence: 99%
“…71 Furthermore, although the majority of people with dementia wish to know the diagnosis, 72 GPs can be reluctant to fully disclose it. 12,73,74 Secondly, GPs may be reluctant to initiate a conversation about BPSD unless they feel comfortable giving practical advice to family caregivers on managing BPSD, something many GPs struggle with. 12 From the findings of this review, inappropriate antipsychotic prescribing appears to be a relevant and worthwhile behaviour to target.…”
Section: Discussionmentioning
confidence: 99%
“…Greater likelihood of telling the diagnosis was associated with the practitioner being male (Somme et al, 2013, Cody et al, 2002 and younger (Somme et al, 2013, Tarek et al, 2009, Downs et al, 2002, or working in a practice with two or more practitioners (Van Hout et al, 2006). Two studies reported contradictory findings on how severity of dementia related to whether the diagnosis was told.…”
Section: Proportion Of Practitioners Who Communicated the Diagnosismentioning
confidence: 99%
“…It is estimated that one-third of GPs lack confidence in their diagnostic skills, while two-thirds lack confidence in the management of behaviours associated with dementia,7 or feel they have little or nothing to offer patients presenting with dementia,13 with a third of GPs failing to routinely disclose the diagnosis 7 14 15. Similarly, pessimism surrounding dementia prognosis, and inability to offer curative treatment16 may lead to an attitude of ‘therapeutic nihilism’ among GPs,7 11 which reflects a biomedical definition of treatment and an ethos centred around curing people,16 while simultaneously ignoring therapeutic interventions that may benefit people with dementia and their carers 17–19…”
Section: Introductionmentioning
confidence: 99%
“…While social psychological theory suggests a relationship between perceptions of self-efficacy, effort and avoidance,22 GPs hesitancy to diagnose dementia may not be explicit. Rather it may manifest in a reluctance to formalise a diagnosis or preferentially treat co-occurring conditions for which treatment options are available,10 23 referring on because of limited treatment options,24 questioning the (traditional) role of the GP in treating dementia25 or having insufficient resources 15…”
Section: Introductionmentioning
confidence: 99%